Pengaruh Upah Minimum, Investasi, dan Belanja Pemerintah terhadap Tingkat Pengangguran di Provinsi Banten Periode 2006-2020 - Muhamad Saiful Islam Zulfikar; Meidy Haviz (UNISBA Press, 2022)
Abstract. This study aims to determine the effect of the minimum wage, investment, and government spending on the unemployment rate in Banten Province for the period 2006-2020. Indonesia's open unemployment rate is spread across every province in Indonesia. One of them is Banten Province. Looking at the Banten area, based on BPS data, it is indicated that the unemployment rate in Banten Province is the highest in Indonesia since 2018-2019 with a percentage rate of 8.47 and 8.11% and the second highest in Indonesia after DKI Jakarta in 2020 with a percentage of 10, 64 percent. The research method used is a quantitative descriptive approach with time series data. The analysis model is using the OLS (Ordinary Least Square) model. The data collection technique used is secondary data from BPS Banten Province, and the Ministry of Finance. The results of the study show that the effect of the minimum wage, investment, and government spending variables on unemployment in Banten Province can be seen from the probability value of the partial test and the simultaneous test. The partial estimation results obtained that the minimum wage (X1) has no significant effect and is positively related to the unemployment rate (Y) in Banten Province at a significance level of 5%. The second variable, investment (X2) has a significant and positive relationship to the open unemployment rate (Y) in Banten Province at a significance level of 5%. The third variable, government or regional spending (X3) in Banten Province has a significant and negative effect on the open unemployment rate (Y) in Banten Province at a significance level of 5%. Meanwhile, the results of the simultaneous test show that the three independent variables (minimum wage, investment, and government spending) simultaneously have a significant effect on the unemployment rate in Banten Province at the 95% confidence level. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh upah minimum, investasi, dan belanja pemerintah terhadap tingkat pengangguran di Provinsi Banten periode 2006-2020. Tingkat pengangguran terbuka Indonesia tersebar disetiap provinsi di Indonesia. Salah satunya Provinsi Banten. Menilik pada daerah Banten, berdasarkan data BPS, terindikasi bahwa tingkat pengangguran di Provinsi Banten merupakan tertinggi di Indonesia sejak 2018-2019 dengan tingkat persentase 8,47 dan 8,11% dan tertinggi kedua di Indonesia setelah DKI Jakarta di tahun 2020 dengan persentasi 10,64 persen. Metode penelitian yang dipakai menggunakan pendekatan deskripstif kuantitatif dengan data time series. Adapun Model analisis yakni menggunakan model OLS (Ordinary Least Square). Teknik pengumpulan data yang diambil adalah data sekunder yang berasal dari BPS Provinsi Banten, dan Kemenkeu. Hasil penelitian menunjukkan pengaruh yang diberikan oleh variabel upah minimum, investasi, dan belanja pemerintah terhadap pengangguran di Provinsi Banten dapat dilihat dari nilai probabilitas uji parsial dan uji simultan. Hasil estimasi secara parsial diperoleh upah minimum (X1) tidak berpengaruh signifikan dan berhubungan positif terhadap tingkat pengangguran (Y) di Provinsi Banten pada tingkat signifikansi 5%. Variabel kedua, investasi (X2) berpengaruh signifikan dan berhubungan positif terhadap tingkat pengangguran terbuka (Y) di Provinsi Banten pada tingkat signifikansi 5%. Variabel ketiga, belanja pemerintah atau daerah (X3) di Provinsi Banten berpengaruh signifikan dan berhubungan negatif terhadap tingkat pengangguran terbuka (Y) di Provinsi Banten pada tingkat signifikansi 5%. Sedangkan, hasil penelitian uji simultan menunjukkan bahwa ketiga variabel independen (upah minimum, investasi, dan belanja pemerintah) secara bersamaan berpengaruh signifikan terhadap tingkat pengangguran di Provinsi Banten pada tingkat kepercayaan 95%.